(untitled) (Ornitología Colombiana, 2021)
The Brown nunlet (N. brunnea) is one of six species of small puffbirds in the genus Nonnula. Here, we describe a nest of Brown Nunlet from Amazonian Ecuador. The nests’ architecture iverges from that of other bucconids, built neither in a subterranean burrow nor in a termitarium, but rather is a flattened, dome-shaped structure composed of leaf litter above a shallow depression. Structural integrity of the leafy dome is created with carefully placed sticks and the inner chamber is entered through a short tunnel. We also provide observations that clarify uncertainties in nest placement of White-chested Puffbird (Malacoptila fusca) and observations on the breeding of other Bucconidae in Amazonian Ecuador.